Physiological Indicators of the Cognitive Redline. (September 2015) - Paras, Carolina Rodriguez; Yang, Shiyan; Tippey, Kathryn; Ferris, Thomas K.
As suggested in recent research, some physiological measures such as breath rate, heart rate, heart rate variability, electroencephalography, and skin conductance response, can be used to indicate aspects of mental workload. Some of these physiological measures are insensitive to added mental workload at a point referred to as the cognitive redline. This redline is not well indicated in the literature, but is generally defined by patterns of performance decrements. The present study involved the use of the Multi-Attribute Task Battery-II (MATB-II) to systematically manipulate imposed multitask workload, and investigate the validity of online measures of heart rate variability (HRV) to indicate the cognitive redline, as inferred by performance and subjective workload measures.